UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETER HASIL HIDROLISIS INFUSA DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DENGAN METODE DPPH (1,1-DIPHENIL-2-PICRYLHYDRAZYL) - Ardianti, Agustina; Guntarti, Any; Zainab, Zainab (Pharmaciana, 2014)
Antioxidant is compounds which have abilities to inhibit oxidation rate. Anredera cordifoliafolium consist of flavonoid which have activities as antioxidant. The purpose of this research was toknow antioxidant activity at ether fraction of hydrolysed aquous extract of Binahong folium (Anrederacordifolia). Ether fraction was obtained by hydrolysing the infuse Binahong folium (Anrederacordifolia) with HCl 2N then fractionated with ether and then evaporated. The antioxidant activity wasmeasured by DPPH method using spectrophotometer. The maximum wavelength and operating timequercetin and samples were 515,0 nm (quersetin) and 514,0 nm (ether fraction), 19-30 minute(quersetin) and 19-29 minute (ether fraction). Scavenging activity test done with the DPPH method(1,1- dyphenyl-2-picrylhydrazyl). The decreasing of DPPH radical solution decreased the absorbantintensity. The percentage of radical scavenging activity was performed as EC50 (EffectiveConcentration). The results indicated that both samples showed free radical scavenging activity withEC50 value for quercetin (2,702±0,15) µg/ml, and ether fraction of (249,31±9,26) µg/ml. Statisticalanalysis using Kruskall Wallis method with 95% of confident level followed by Mann Whitney testgiving evidence the results between samples and positive control (quercetin) are significantlydifference.